Hubungan Antara Agama dan Negara di NKRI Dalam Sorotan Filsafat Politik - Sermada Kelen Donatus (Sekolah Tinggi Widya Sasana, 2023)
The relationship between religion and state in Indonesia does not go on smoothly and well nowadays. The ethics of practicing the religion and of performing the state do not grow up in a healthy way. The purpose of the author writing this article is to urge the Indonesian government to erase the law of blasphemy on religion applied to the life of the Indonesian state. The method the author is using is the way of describing the political facts concerning the ethics of practicing the religion and of performing the Indonesian state and the way of evaluating the distortion availed in the life of practicing the religion and the citizenship from the political theories. From the political point of view it comes to the conclusion that the law of blasphemy on religion in the Indonesian state should be erased